Greenwashing and Sustainable Consumption in India: A Socio-legal Study of Consumer Perception, Behaviour, and the Legal Enforcement Gap - Pooja Devi; Shikha Sharma (Faculty of Law, Sriwijaya University, Indonesia, 2026)
Sustainable marketing has reshaped recent consumption behaviours. As global awareness of green living grows, businesses are gradually promoting the “green badge